An inductorless P-SSHC piezoelectric energy harvesting integrated system with high flipping efficiency. (July 2022) - Liu, Lianxi; Ou, Yuanwen; Ma, Jian; Xie, Yuhang; Yu, Ying
Abstract: This paper presents an inductorless piezoelectric energy harvesting integrated system with high flipping efficiency using P-SSHC. Since the rectifier using parallel synchronized switch harvesting on capacitor (P-SSHC) has a trade-off between the rectification efficiency and the system volume, a voltage flipping optimization method for the parasitic capacitor of the piezoelectric source is proposed in this paper. It sets the proportional relationship between the flipping and parasitic capacitor, achieving optimal voltage flipping efficiency and improving rectification efficiency. In addition, to achieve the miniaturization of the system, this paper uses a switched capacitor (SC) DC/DC converter with a variable voltage conversion ratio (VCR) to replace the traditional inductive type DC/DC converter. The proposed system was implemented in a 0.18 μm BCD process with a core circuit chip area of 1152 × 585 μm 2 . The voltage flipping efficiency of the designed rectifier reaches 74%. The overall system does not use inductors. Within the open-circuit voltage range of 1–1.8 V, it achieves a peak end-to-end conversion efficiency of 81.45% and a peak voltage tracking efficiency of 98.89%.